Ionic-Liquid-Mediated MacMillan’s Catalyst for Diels-Alder Reaction - Vivek Srivastava (Journal of Chemistry)
Ionic liquids were used to enhance as well as recycle the MacMillan's catalyst 1 for the Diels-Alder reaction. Using our developed protocol, Diels-Alder adducts were obtained in good yields and selectivities along the 6 times recycling of MacMillan's imidazolidinone catalyst 1. Synthesis of steroid 4 is the major outcome of our developed protocol.